Experience with voluntary severe acute respiratory coronavirus virus 2 (SARS-CoV-2) testing of asymptomatic staff at the National Institutes of Health for one year. (2nd November 2022) - Totten, Arthur H.; Matlock, Ann Marie; Bailin, Heike; Revoir, Josanne; Siwy, Christopher M.; Joyce, Maria; Coffey, Patricia; Henderson, David K.; Palmore, Tara N.; Frank, Karen M.; McKeeby, Jon
Abstract: Voluntary asymptomatic severe acute respiratory coronavirus virus 2 (SARS-CoV-2) testing was provided by the NIH Clinical Center over 1 year. Among 105, 927 tests, 0.2% were positive. Among eligible staff, 79% participated with variable frequency and 61% of positive individuals had symptoms at the time of testing. Saliva specimen collection was chosen as an option less frequently than midturbinate collection.